Fixed or Flexible? : Getting the Exchange Rate Right in the 1990s - Aziz, Jahangir; Caramazza, Francesco (Washington, D.C. : International Monetary Fund, 1998)
This paper examines the recent evolution of exchange rate policies in the developing world. It looks at why so many countries have made a transition from fixed or "pegged" exchange rates to "managed floating" currencies. It discusses how economics perform under different exchange rate arrangements, issues in the choice of regime, and the challenges poised by a world or increasing capital mobility, especially when banking sectors are inadequately regulated or supervised.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet